Composite Coating Prepared with Ferulic Acid to Improve the Corrosion Resistance and Blood Compatibility of Magnesium Alloy - Zhijin Han; Haojie Guo; Yifan Zhou; Liguo Wang; Kun Zhang; Jing-an Li (Metals, 2022)
Magnesium (Mg) alloy has been used for medical vascular stents because of its good biocompatibility and degradability, but its rapid degradation and poor blood compatibility limits its further application. In this study, ferulic acid (FA) was conjugated onto the polydopamine (PDA) deposited Mg-Zn-Y-Nd alloy to prepare a PDA/FA multi-functional coating with better corrosion resistance and blood compatibility. The results suggest that the PDA/FA coating possessed potential application for surface modification of a medical Mg alloy.